Phytofabrication of silver nanoparticles by using aquatic plant Hydrilla verticillata - NEILESH SABLE; SWAPNIL GAIKWAD; SHITAL BONDE; ANIKET GADE; MAHENDRA RAI (Nusantara Bioscience, 2012)
Abstract. Sable N, Gaikwad S, Bonde S, Gade A, Rai M. 2012. Phytofabrication of silver nanoparticles by using aquatic plant Hydrilla verticillata. Nusantara Bioscience 4: 45-49. In the context of current drive to developed new green technology in nanomaterials, synthesis of nanoparticles is of considerable importance. There has been considerable work done in the field of nanoscience and Nanotechnology during the last decade due to the introduction of various protocols for the synthesis of nanoparticles by using plants and microorganisms. Here we firstly report the extracellular photosynthesis of silver nanoparticles (Ag-NPs) using aquatic plants Hydrilla verticillata. The characterization of the phytosynthesized Ag-NPs was done with the help of UV-Vis spectroscopy, FTIR, Nanoparticle Tracking Analysis (NTA), Zeta potential and SEM. The SEM micrograph revealed the synthesis of polydispersed spherical nanoparticles, with an average size of 65.55 nm. The phytofabricated Ag-NPs can be used in the field of medicine and agriculture, due to their antimicrobial potential.